Complications in shoulder arthroplasty: an analysis of 485 cases - Aldinger, Peter; Raiss, Patric; Rickert, Markus; Loew, Markus (International orthopaedics, 2010)
The aim of this study was to analyse the complication rates of six different shoulder arthroplasty concepts for different diagnoses in the short and midterm. The study included 485 primary shoulder arthroplasties. The mean follow-up of the cohort was 3.5 (1-10) years. Complications were classified into three categories: (1) without reoperation, (2) soft tissue revision and (3) implant revision. In total, 56 complications were recorded (11.6%): 34 (7%) were category 1 complications, 11 (2.3%) were category 2 and 11 (2.3%) were category 3. For the whole cohort the median follow-up was 1.6 years (1-10 years) and the survival rate without any complication was 90.5% (95% CI: 87.9-93.1). Patients rated the result of their surgery in 270 (55.7%) cases as very satisfied, in 148 (30.5%) as satisfied, in 43 (8.9%) as somewhat disappointed and in 24 (4.9%) as disappointed. A relatively low complication rate was found in this study. Long-term observations are necessary to confirm these results.
Online veröffentlicht: 28 April 2009
Gesehen am 17.11.2022